STRATEGI TIM PEMENANGAN DALAM MEMENANGKAN PASANGAN AFRIZAL SINTONG S.I.P DENGAN H. SULAIMAN, SS. MH PADA PILKADA SERENTAK KAB. ROKAN HILIR TAHUN 2020 - Laksana, Arif Sedia; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Strategy is a method used to win the candidate pairs that are carried. In order to win a candidate in the election, political parties should as far as possible target a number of votes that will exceed the votes of other candidate pairs. This study aims to determine the strategy of the coalition parties in winning the pair of regent and deputy regent candidates Afrizal Sintong S.IP and H.Sulaiman, SS. MH in the local elections in Rokan Hilir Regency. While the methodology used in the preparation of this thesis uses qualitative methods, namely interviews with relevant sources in winning candidate pairs, then collects data, organizes and classifies data, the analysis is descriptive in nature which describes the strategic steps carried out by the coalition parties in the general election of the district head Rokan Hilir in 2020. to explain the meaning of politics to voters by using defensive and offensive strategies then this offensive strategy was developed by taking approaches namely push marketing, pull marketing, and pass marketing, this approach was used to promote the candidate pair Afrizal and H. Sulaiman. There are several strategic things carried out by the winning coalition party Afrizal and H. Sulaiman. First, in their defensive strategy, they mapped the mass base, which strengthened the estimated mass, which was certain to choose a candidate pair because of environmental and emotional factors with the candidate pair's personality. Second, with an offensive strategy, the winning team introduced or socialized the pairs of candidates for regent and deputy regent through the outskirts of the Rokan downstream district with the aim of focusing on voters who were far away from other pairs. Third, optimizing the role of social media such as Facebook and Instagram to carry out campaigns. KEYWORDS: Strategy, Winning Team, Rokan Hilir Pilkada